Method for volume reduction and solidification treatment of radioactive waste thermal insulation cotton

CN123033796APending Publication Date: 2026-11-03CHINA INST FOR RADIATION PROTECTION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611115970.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies are difficult to effectively process aluminum silicate insulation cotton waste with high aluminum content, resulting in long-term storage occupying large storage space and posing a risk of radioactive nuclide leakage. Incineration and plasma melting technologies are costly and have limited volume reduction effects.

Method used

Alkali metal salts and boron compounds, or alkali metal chlorides and alkaline earth metal chlorides, are used as additives. After being mixed with thermal insulation cotton, they are hot-pressed and heated a second time to form a glass-cured body. High-efficiency volume reduction is achieved by controlling the heating rate and pressure.

Benefits of technology

It achieves a high volume reduction ratio (2-3) and a nuclide leaching rate that complies with national regulations, reducing the challenges of radioactive waste management and avoiding the need for high-cost plasma furnaces and glass charge unloading systems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a kind of radioactive waste thermal insulation cotton volume reduction and solidification processing method, comprising the following steps: thermal insulation cotton and additive are mixed, and obtain mixed raw material, the additive is the mixture of alkali metal salt and boron compound, or the mixture of alkali metal chloride and alkaline earth metal chloride;The mixed raw material is heat-pressed forming, and waste block is obtained;The waste block is removed from the die of the heat-pressed forming, then, the waste block is heated again to higher than heat-pressed forming temperature, and then, it is kept warm to obtain solidification body;After the solidification body is cooled, blocky glass solidification body is obtained, and processing is completed.The present application compared with plasma melting technology, without the construction cost of high plasma furnace and glass material discharge system can reach close volume reduction effect, and economic value is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radioactive waste treatment technology, and in particular to a method for reducing the volume and solidifying radioactive waste insulation cotton. Background Technology

[0002] Alumina silicate insulation materials are widely used in nuclear power, especially in early domestically constructed reactor types, primarily as thermal insulation materials covering the perimeter of reactor pressure tanks and pipeline surfaces. With technological advancements, some pressurized water reactors have replaced their insulation materials with metal reflective insulation materials. However, in fourth-generation reactors, due to the increased primary loop temperature, insulation materials primarily composed of alumina silicate fibers have been widely reintroduced and are now being widely used again.

[0003] Currently, the primary method for handling low-radioactivity aluminosilicate insulation materials generated by nuclear power plants worldwide is still temporary storage. While technologies such as plasma melting, compression cement solidification, and high-temperature melting have been developed both domestically and internationally to address this waste, they remain largely in the laboratory stage and have not been widely applied due to technological and economic limitations. High-temperature melting involves grinding waste insulation materials into powder, mixing it with potassium carbonate, and melting it at around 700°C to form a vitrified body. However, this technology is only suitable for insulation materials primarily composed of silica, such as perlite. It cannot effectively vitrify waste materials with high aluminum content (e.g., Al2O3 (alumina) content of 40-60% by mass) such as aluminosilicate insulation cotton. Long-term storage of insulation materials requires significant storage space in waste storage containers, and because radioactive nuclides are not fixed, there is a certain risk of radioactive nuclide leakage during temporary storage. The high-temperature duration of incineration is too short, only 1-5 seconds, and requires 30-60% combustible material, while insulation materials are non-combustible, resulting in extremely limited volume reduction and the need for secondary treatment. Alternatively, megawatt-level heating equipment can be used to generate plasma for high-temperature treatment of waste insulation materials, but the plasma torch has a short lifespan and requires complex exhaust gas purification facilities, leading to high construction and maintenance costs. These problems urgently need to be addressed. Summary of the Invention

[0004] This invention discloses a method for reducing the volume and solidifying radioactive waste insulation cotton, aiming to solve the technical problems existing in the prior art.

[0005] The present invention adopts the following technical solution: This invention provides a method for reducing the volume and solidifying radioactive waste insulation cotton, which includes the following steps: The thermal insulation cotton and the additives are mixed to obtain a mixed raw material, wherein the additives are a mixture of alkali metal salts and boron compounds, or a mixture of alkali metal chlorides and alkaline earth metal chlorides. The mixed raw materials are hot-pressed to form waste blocks; The waste block is removed from the hot-pressing mold, and then the waste block is reheated to a temperature higher than the hot-pressing temperature and held at that temperature to obtain a solidified body. After cooling the cured body, a block-shaped glass cured body is obtained, and the processing is complete.

[0006] In the method for reducing and solidifying the volume of radioactive waste insulation cotton of the present invention, the step of hot-pressing the mixed raw materials to obtain waste blocks includes: The mixed raw materials are sequentially and continuously hot-pressed under the first and second conditions, and after hot pressing is completed under the second condition, the material is kept at the temperature for 1-3 hours. The first condition is to heat to 500°C at a heating rate of 5-10°C / min and to form a pressure of 3-10 tons. The second condition is to heat to 750°C at a heating rate of 5-15°C / min and to form a pressure of 5-15 tons.

[0007] In the method for reducing the volume and solidifying radioactive waste insulation cotton of the present invention, the step of heating the waste block to 950℃-1000℃ and then holding it at that temperature to obtain a solidified body includes: The waste block is heated to 950°C at a heating rate of 10-20°C / min, and the flow rate of the gas overflowing from the waste block is monitored. When the flow rate drops by more than 50%, the temperature is further increased to 1000°C and held for 1 hour to obtain a solidified body.

[0008] In the method for reducing and solidifying radioactive waste insulation cotton of the present invention, the step of cooling the solidified body to obtain a block-shaped glass solidified body includes: The cured body was cooled to 200°C at a cooling rate of 80–100°C / min, and then allowed to cool naturally to room temperature to obtain a block-shaped glass cured body.

[0009] In the method for reducing the volume and solidifying radioactive waste insulation cotton of the present invention, the mass ratio of the insulation cotton to the additive is 1:1-1:3.

[0010] In the method for reducing the volume and solidifying radioactive waste insulation cotton of the present invention, the alkali metal salt includes one or more of lithium salt, sodium salt and potassium salt.

[0011] In the method for reducing the volume and solidifying radioactive waste insulation cotton of the present invention, the alkali metal salt is an alkali metal carbonate, nitrate, or oxide; and the boron compound is boron oxide.

[0012] In the method for reducing the volume and solidifying radioactive waste insulation cotton of the present invention, the additive includes the following components by weight percentage: 5-40% Li2CO3, 5-30% Na2CO3, 5-30% K2CO3 and 10-40% B2O3.

[0013] In the method for reducing the volume and solidifying radioactive waste insulation cotton of the present invention, the alkali metal chloride is selected from one or more of lithium chloride, sodium chloride and potassium chloride; The alkaline earth metal chloride is selected from calcium chloride, magnesium chloride, strontium chloride, or barium chloride.

[0014] In the method for reducing and solidifying the volume of radioactive waste insulation cotton of the present invention, the lithium chloride content is 20%, the sodium chloride content is 20%, the potassium chloride content is 25%, and the calcium chloride content is 35% by mass percentage.

[0015] The technical solution adopted in this invention can achieve the following beneficial effects: This invention provides a method for reducing the volume and solidifying radioactive waste insulation cotton. It involves mixing insulation cotton with additives composed of alkali metal salts and boron compounds, or alkali metal chlorides and alkaline earth metal chlorides, followed by hot pressing. Combined with hot pressing and secondary heating, this method can transform aluminum silicate insulation cotton with high aluminum content into a glass solid, achieving a high volume reduction ratio (2-3). Simultaneously, the radionuclide leaching rate meets national regulatory requirements, reducing the difficulties in the later management of radioactive waste. Furthermore, compared to plasma melting technology, it achieves a similar volume reduction effect without the need for costly plasma furnaces and glass discharge systems, resulting in higher economic value. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. In the description of this invention, it should be noted that the term "or" is generally used to include the meaning of "and / or," unless otherwise expressly indicated.

[0017] Unless explicitly stated otherwise, the numerical parameters in this specification and the appended claims may be approximate values ​​and can be varied according to the desired characteristics obtained from the content of this invention. Specifically, all figures used in the specification and claims to indicate the content of composition, reaction conditions, etc., should be understood to be modified by the term "about" in all cases. Generally, this means that there may be variations of ±10% in some embodiments, ±5% in some embodiments, ±1% in some embodiments, and ±0.5% in some embodiments.

[0018] Furthermore, the word "comprising" does not exclude the presence of materials or steps not listed in the claims. The ordinal numbers used in the specification and claims, such as "first," "second," "third," and Arabic numerals and letters, to modify corresponding elements or steps, do not in themselves imply an order of manufacturing process; their use is solely to ensure clear distinction between steps.

[0019] Furthermore, unless specifically described or required to occur in a specific order, the order of the above steps is not limited to those listed above and can be varied or rearranged according to the desired design. Moreover, the above embodiments can be used in combination with each other or with other embodiments based on design and reliability considerations; that is, technical features from different embodiments can be freely combined to form more embodiments.

[0020] Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0021] To address the problems existing in the prior art, this application provides a method for reducing the volume and solidifying radioactive waste insulation cotton.

[0022] A method for reducing the volume and solidifying radioactive waste insulation cotton, comprising the following steps: Insulation cotton and additives are mixed to obtain a mixed raw material. The additives are a mixture of alkali metal salts and boron compounds, or a mixture of alkali metal chlorides and alkaline earth metal chlorides. The mixed raw material is hot-pressed to obtain a waste block. The waste block is removed from the hot-pressing mold, and then the waste block is reheated to a temperature higher than the hot-pressing temperature and held at that temperature to obtain a solidified body. After the solidified body is cooled, a block-shaped glass solidified body is obtained, and the process is complete.

[0023] This invention discloses a method for reducing the volume and solidifying radioactive waste insulation cotton. The method involves mixing insulation cotton with additives composed of alkali metal salts and boron compounds, or alkali metal chlorides and alkaline earth metal chlorides, followed by hot pressing. Combined with hot pressing and secondary heating, this method can transform aluminum silicate insulation cotton with high aluminum content into a glass solid, achieving a high volume reduction ratio (2-3). Simultaneously, the radionuclide leaching rate meets national regulatory requirements, reducing the difficulties in the later management of radioactive waste. Furthermore, compared to plasma melting technology, it achieves a similar volume reduction effect without the need for costly plasma furnaces and glass discharge systems, resulting in higher economic value.

[0024] In some preferred embodiments, the step of hot-pressing the mixed raw materials to obtain waste blocks includes: sequentially hot-pressing the mixed raw materials under first and second conditions, and holding the mixture at a constant temperature for 1-3 hours after hot-pressing under the second condition; the first condition is heating to 500°C at a heating rate of 5-10°C / min, with a molding pressure of 3-10 tons; the second condition is heating to 750°C at a heating rate of 5-15°C / min, with a molding pressure of 5-15 tons. Based on first hot-pressing under the first condition, during which the additives melt and impregnate the aluminosilicate fibers under pressure, and then hot-pressing under the second condition, the pressure drives the molten additives to penetrate the fiber gaps, and alkali metal ions rapidly break the Si-O-Al bonds; furthermore, limiting the hot-pressing temperature to 750°C avoids adhesion to the mold or incomplete fiber dissociation reaction during waste block transfer.

[0025] In some preferred embodiments, the step of heating the waste block to 950℃-1000℃ and holding it at that temperature to obtain a cured body includes: heating the waste block to 950℃ at a heating rate of 10-20℃ / min, monitoring the flow rate of the gas escaping from the waste block, and when the flow rate drops by more than 50%, continuing to heat to 1000℃ and holding at that temperature for 1 hour to obtain a cured body. This method first heats the waste block to 950℃ to melt it, and then uses additives to participate in the reconstruction of the silicon-oxygen network to form a uniform multi-element silicate melt. Then, heating to 1000℃ allows the residual tiny CO2 bubbles in the melt to escape, improving the quality of the glass cured body. The temperature in this process should not be too low, as this may lead to incomplete reaction and affect the performance of the cured body.

[0026] In some preferred embodiments, the step of obtaining a block-shaped glass-cured body after cooling the cured body includes: cooling the cured body to 200°C at a cooling rate of 80–100°C / min, and then allowing it to cool naturally to room temperature, thereby reducing the risk of crystallization and obtaining a block-shaped glass-cured body. Based on this, the cured body can be cooled uniformly, avoiding internal stress.

[0027] In some preferred embodiments, the mass ratio of insulation cotton to additives is 1:1 to 1:3. Outside this range, the volume reduction ratio decreases.

[0028] In some preferred embodiments, the alkali metal salt includes one or more of lithium, sodium, and potassium salts.

[0029] Preferably, the alkali metal salt is an alkali metal carbonate, nitrate, or oxide; the boron compound is boron oxide.

[0030] In some preferred embodiments, the additives include the following components in weight percentages: 5-40% Li2CO3, 5-30% Na2CO3, 5-30% K2CO3 and 10-40% B2O3.

[0031] In some preferred embodiments, the alkali metal chloride is selected from one or more of lithium chloride, sodium chloride and potassium chloride; the alkaline earth metal chloride is selected from calcium chloride or magnesium chloride or strontium chloride or barium chloride.

[0032] Specifically, the combination of alkali metal chlorides and alkaline earth metal chlorides can be: Binary eutectic chlorides include lithium chloride-calcium chloride, lithium chloride-magnesium chloride, sodium chloride-calcium chloride, potassium chloride-calcium chloride, potassium chloride-strontium chloride, and potassium chloride-barium chloride; their mass ratios are LiCl 32%+CaCl2 68%, LiCl 44%+MgCl2 56%, NaCl 48%+CaCl2 52%, KCl 56%+CaCl2 44%, KCl 53%+SrCl2 47%, and KCl 51%+BaCl2 49%, respectively. The ternary low-melting-point chlorides are selected from lithium chloride-sodium chloride-calcium chloride, sodium chloride-potassium chloride-calcium chloride, lithium chloride-potassium chloride-magnesium chloride, and sodium chloride-potassium chloride-strontium chloride; the corresponding mass ratios are LiCl 25%+NaCl 20%+CaCl2 55%, NaCl 30%+KCl 30%+CaCl2 40%, LiCl 40%+KCl 30%+MgCl2 30%, and NaCl 28%+KCl 32%+SrCl2 40%. The quaternary complex chloride comprises lithium chloride, sodium chloride, potassium chloride, and calcium chloride, with a mass ratio of 20% LiCl, 20% NaCl, 25% KCl, and 35% CaCl2.

[0033] In some preferred embodiments, the particle size of the insulation cotton is less than or equal to 10 mm.

[0034] In some preferred embodiments, the activity concentration and radionuclide types of waste insulation cotton are confirmed through source term investigation. For some waste insulation cotton with high activity concentration and short-lived radionuclide types, the activity concentration can be further reduced through temporary decay (the specific activity concentration value can be determined according to specific needs to ensure the safety of operators), thereby ensuring the safety of operators.

[0035] The following examples and comparative examples all involve aluminum silicate insulation cotton with a high aluminum content (e.g., 40-60% by mass).

[0036] Example 1 Thermal insulation cotton and additives were mixed at a mass ratio of 1:2 to obtain a mixed raw material. The additive composition was 20% lithium carbonate, 20% sodium carbonate, 25% potassium carbonate, and 35% calcium carbonate. The mixed raw materials are placed in a hot press molding mold and pressurized to 10 tons. While pressurizing, the temperature is increased to 500℃ at a rate of 8℃ / min. Then, the pressure is increased to 15 tons and the temperature is increased to 750℃ at a rate of 10℃ / min. The mixture is then kept at this temperature for 3 hours. Remove the waste block from the hot-pressed mold, then place the waste block into a sealed furnace with vents, and heat it to 950°C at a heating rate of 15°C / min. During this process, check the gas flow rate escaping from the vents. When the flow rate drops by more than 50%, continue heating to 1000°C, and then hold it at that temperature for one hour to obtain the solidified body. The cured body was cooled to 200°C at a cooling rate of 90°C / min, and then allowed to cool naturally to room temperature to obtain a block-shaped glass cured body. The process was then complete.

[0037] Calculations show that the leaching rate of the glass-cured body obtained in this embodiment is Cs: 4 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 6×10 -4 g·m -2 ·d -1 The leaching rate can be measured with reference to standard GB / T4960.8—2025.

[0038] Example 2 Thermal insulation cotton and additives were mixed at a mass ratio of 1:3 to obtain a mixed raw material. The additive composition was 5% lithium carbonate, 30% sodium carbonate, 30% potassium carbonate, and 35% calcium carbonate. The mixed raw materials are placed in a hot press molding mold, pressurized to 3 tons, and then heated to 500℃ at a heating rate of 10℃ / min. Then, the pressure is increased to 5 tons, and the temperature is increased to 750℃ at a heating rate of 15℃ / min. Then, the temperature is maintained for 3 hours. Remove the waste block from the hot-pressed mold, then place the waste block into a sealed furnace with vents, and heat it to 950°C at a heating rate of 20°C / min. During this process, check the gas flow rate escaping from the vents. When the flow rate drops by more than 50%, continue heating to 1000°C, and then hold it at that temperature for one hour to obtain the solidified body. The cured body was cooled to 200℃ at a cooling rate of 100℃ / min, and then allowed to cool naturally to room temperature to obtain a block-shaped glass cured body. The process was then complete.

[0039] The leaching rate of the glass-cured body obtained in this embodiment, Cs, is calculated to be 8.7 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 9.5 × 10 -4 g·m -2·d -1 .

[0040] Example 3 Thermal insulation cotton and additives were mixed at a mass ratio of 1:1 to obtain a mixed raw material. The additive composition was 40% lithium carbonate, 5% sodium carbonate, 20% potassium carbonate, and 35% calcium carbonate. The mixed raw materials are placed in a hot press molding mold, pressurized to 10 tons, then heated to 500℃ at a heating rate of 5℃ / min, then pressurized to 15 tons, heated to 750℃ at a heating rate of 5℃ / min, and then held at that temperature for 3 hours. Remove the waste block from the hot-pressed mold, then place the waste block into a sealed furnace with vents, and heat it to 950°C at a heating rate of 10°C / min. During this process, check the gas flow rate escaping from the vents. When the flow rate drops by more than 50%, continue heating to 1000°C, and then hold it at that temperature for one hour to obtain the solidified body. The cured body was cooled to 200°C at a cooling rate of 80°C / min, and then allowed to cool naturally to room temperature to obtain a block-shaped glass cured body. The process was then complete.

[0041] The leaching rate of the glass-cured body obtained in this embodiment, Cs, was calculated to be 3.1 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 5.4 × 10 -4 g·m -2 ·d -1 .

[0042] Example 4 The difference between this embodiment and Embodiment 1 is that the additive composition is 40% lithium chloride, 30% sodium chloride, 5% potassium chloride, and 25% calcium chloride; the rest is the same as in Embodiment 1.

[0043] The leaching rate of the glass-cured body obtained in this embodiment, Cs, was calculated to be 9.4 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 1.2 × 10 -3 g·m -2 ·d -1 .

[0044] Example 5 The difference between this embodiment and Embodiment 1 is that the additive composition is 40% lithium chloride, 30% sodium chloride, 20% potassium chloride, and 10% calcium chloride; the rest is the same as in Embodiment 1.

[0045] The calculated leaching rate of the glass-cured body obtained in this embodiment is Cs: 1.1 × 10⁻⁶.-1 g·m -2 ·d -1 Sr: 1.5×10 -3 g·m -2 ·d -1 .

[0046] Example 6 The difference between this embodiment and Embodiment 1 is that the additive composition is 20% lithium chloride, 45% potassium chloride, and 35% calcium chloride; the rest is the same as in Embodiment 1.

[0047] The leaching rate of the glass-cured body obtained in this embodiment, Cs, was calculated to be 1.3 × 10⁻⁶. -1 g·m -2 ·d -1 Sr: 1.7 × 10 -3 g·m -2 ·d -1 .

[0048] Example 7 The difference between this embodiment and Embodiment 1 is that the additive composition is 28% sodium chloride, 32% potassium chloride, and 40% strontium chloride; the rest is the same as in Embodiment 1.

[0049] The leaching rate of the glass-cured body obtained in this embodiment, Cs, was calculated to be 1.0 × 10⁻⁶. -1 g·m -2 ·d -1 Sr: 8.3×10 -4 g·m -2 ·d -1 .

[0050] Comparative Example 1 The difference between this comparative example and Example 1 is that the mass ratio of thermal insulation cotton to additives is 1:4; the rest is the same as in Example 1.

[0051] The calculated leaching rate of the glass-cured body obtained in this comparative example is Cs: 7.9 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 8.8 × 10 -4 g·m -2 ·d -1 .

[0052] Comparative Example 2 The difference between this comparative example and Example 1 is that the mass ratio of thermal insulation cotton to additives is 2:1; otherwise, it is the same as Example 1.

[0053] The leaching rate of the glass-cured body obtained in this comparative example is calculated to be Cs: 1.6 × 10⁻⁶. -1 g·m -2 ·d-1 Sr: 2.1×10 -3 g·m -2 ·d -1 .

[0054] Comparative Example 3 The difference between this comparative example and Example 1 is that the maximum hot pressing temperature is 800°C; otherwise, it is the same as Example 1.

[0055] The leaching rate of the glass-cured body obtained in this comparative example is calculated to be Cs: 5.1 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 6.8 × 10 -4 g·m -2 ·d -1 .

[0056] Comparative Example 4 The difference between this comparative example and Example 1 is that the secondary heating temperature is 1200℃; otherwise, it is the same as Example 1.

[0057] The leaching rate of the glass-cured body obtained in this comparative example is calculated to be Cs: 5.6 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 6.5 × 10 -4 g·m -2 ·d -1 .

[0058] Comparative Example 5 The difference between this comparative example and Example 1 is that the secondary heating temperature is 900°C; otherwise, it is the same as Example 1.

[0059] The leaching rate of the glass-cured body obtained in this comparative example is calculated to be Cs: 9.1 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 1.1×10 -3 g·m -2 ·d -1 .

[0060] Comparative Example 6 The difference between this comparative example and Example 1 is that the temperature was directly raised to 750°C at a heating rate of 8°C / min during the hot pressing process; the rest is the same as Example 1.

[0061] The leaching rate of the glass-cured body obtained in this comparative example is calculated to be Cs: 7.4 × 10⁻⁶. -2 g·m -2 ·d -1 Sr: 8.2×10 -4 g·m -2·d -1 .

[0062] The embodiments of the present invention have been described above. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of the present invention.

Claims

1. A method for reducing the volume and solidifying radioactive waste insulation cotton, characterized in that, Includes the following steps: The thermal insulation cotton and the additives are mixed to obtain a mixed raw material, wherein the additives are a mixture of alkali metal salts and boron compounds, or a mixture of alkali metal chlorides and alkaline earth metal chlorides. The mixed raw materials are hot-pressed to form waste blocks; The waste block is removed from the hot-pressing mold, and then the waste block is reheated to a temperature higher than the hot-pressing temperature and held at that temperature to obtain a solidified body. After cooling the cured body, a block-shaped glass cured body is obtained, and the processing is complete.

2. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 1, characterized in that, The step of hot-pressing the mixed raw materials to obtain waste blocks includes: The mixed raw materials are sequentially and continuously hot-pressed under the first and second conditions, and after hot pressing is completed under the second condition, the material is kept at the temperature for 1-3 hours. The first condition is to heat to 500°C at a heating rate of 5-10°C / min and to form a pressure of 3-10 tons. The second condition is to heat to 750°C at a heating rate of 5-15°C / min and to form a pressure of 5-15 tons.

3. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 1, characterized in that, The step of heating the waste block to 950℃-1000℃ and then holding it at that temperature to obtain a solidified body includes: The waste block is heated to 950°C at a heating rate of 10-20°C / min, and the flow rate of the gas overflowing from the waste block is monitored. When the flow rate drops by more than 50%, the temperature is further increased to 1000°C and held for 1 hour to obtain a solidified body.

4. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 1, characterized in that, The step of cooling the cured body to obtain a block-shaped glass cured body includes: The cured body was cooled to 200°C at a cooling rate of 80–100°C / min, and then allowed to cool naturally to room temperature to obtain a block-shaped glass cured body.

5. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 1, characterized in that, The mass ratio of the thermal insulation cotton to the additive is 1:1 to 1:

3.

6. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 1, characterized in that, The alkali metal salt includes one or more of lithium, sodium, and potassium salts.

7. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 1, characterized in that, The alkali metal salt is an alkali metal carbonate, nitrate, or oxide; the boron compound is boron oxide.

8. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 7, characterized in that, The additive comprises the following components by weight percentage: 5-40% Li2CO3, 5-30% Na2CO3, 5-30% K2CO3 and 10-40% B2O3.

9. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 1, characterized in that, The alkali metal chloride is selected from one or more of lithium chloride, sodium chloride, and potassium chloride; The alkaline earth metal chloride is selected from calcium chloride, magnesium chloride, strontium chloride, or barium chloride.

10. The method for reducing and solidifying the volume of radioactive waste insulation cotton according to claim 9, characterized in that, The lithium chloride content is 20% by mass percentage, the sodium chloride content is 20%, the potassium chloride content is 25%, and the calcium chloride content is 35%.